Потерянные записки о Шерлоке Холмсе: [рассказы] / Пол Д. Гилберт - Гилберт Пол Д. (GELEOS, 2007)
Экземпляры: КХ (20180531) / Инвентарный номер: 1103589 / Цена: / Сис.шифр: И(Англ) / Авт.знак: Г 47 / ГРНТИ: 17 / ББК: 84(4/8)